A re-examination of Tuta absoluta parasitoids in South America for optimized biological control - Salas Gervassio, Nadia Gisela (2019)
We conducted a review of published information on Tuta absoluta parasitoids for the Neotropical region to (1) corroborate species records, (2) analyze associations including the T. absoluta, other insect and plant hosts and (3) identify research directions for enhancing their use as biological control agents. The literature review shows more than 50 species or morphospecies of Hymenoptera associated with T. absoluta, but less than a half (23) could be confirmed as parasitizing T. absoluta. Erroneous reports or invalid names of species, two new species records were found. Over a 100 pests and non-economically important insect and cultivated and non-cultivated plants directly or indirectly interact with T. absoluta in the region. Four T. absoluta parasitoid species include in their host range predatory insects or act as hyperparasitoids, a negative feature considered for a biological control agent. Five larval parasitoids have a narrow host range and could be considered for classical biological control programs in the areas of new invasion. Six Trichogrammatidae species are commercially used in various countries; of those, T. minutum and T. pretiosum are considered to be moderately generalist, being able to exploit several insect hosts. Apart from Apanteles gelechiidivoris and Pseudapanteles dignus, other native species have been the subject of field studies as biological control agents. The review presented here provides useful insights for identifying species that deserve further evaluation as T. absoluta biological control agents through augmentative or conservation strategies in South America, as well as for potential classical biological control programs in other continents.